RECENT TRENDS IN HUMAN RESOURCE MANAGEMENT IN THE DIGITAL AGE - Hery Purnomo; Subagyo, Faisol, Dodi Kusuma Hadi Soejoko, Poniran Yudho Leksono (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Human Resource (HR) management in the digital age is undergoing a significant transformation, characterised by the integration of advanced technologies and a paradigm shift in the approach to the workforce. This study examines current trends in HR management, highlighting the role of artificial intelligence, data analytics and digital platforms in optimising HR processes. Findings indicate a shift in focus towards holistic employee experiences, continuous learning and work flexibility. While technology plays an important role, the research emphasises the importance of maintaining a balance between technological efficiency and the human element in building a strong organisational culture. In conclusion, successful HR management in the digital age depends on an organisation's ability to integrate technological innovation with people- centric strategies, creating an engaged, productive and innovative work environment.